2008
DOI: 10.1186/1472-6882-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise therapy on lipid profile and oxidative stress indicators in patients with type 2 diabetes

Abstract: Background: Yoga has been shown to be a simple and economical therapeutic modality that may be considered as a beneficial adjuvant for type 2 diabetes mellitus. This study investigated the impact of Hatha yoga and conventional physical training (PT) exercise regimens on biochemical, oxidative stress indicators and oxidant status in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(111 citation statements)
references
References 54 publications
4
102
0
3
Order By: Relevance
“…It has been proposed that lipid peroxidation products, i.e., MDA levels, as indicator of oxidative stress, increase significantly in patients with OA [38,39]. Moreover, it has been reported that plasma TAC levels are significantly lower in OA patients compared to healthy subjects [40].…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed that lipid peroxidation products, i.e., MDA levels, as indicator of oxidative stress, increase significantly in patients with OA [38,39]. Moreover, it has been reported that plasma TAC levels are significantly lower in OA patients compared to healthy subjects [40].…”
Section: Discussionmentioning
confidence: 98%
“…Whoever the one session of intense physical activity increased the oxidative stress marker (15,16), the long period of resistance training can so to change the physiological body response to oxidative stress situation that the ample of oxidative stress and production of free radicals and oxidative productions decrease in rest and physical activity state. Research finding, however usually support from the reduction effect of long period of resistance training (17,18), some researches signify to lack of change (19) and even the increase of oxidative stress, on the effect of long periods of resistance training (14). This inconsistent results may be the result of different conditions of training periods, in terms of intensity and training duration or the different subject conditions in terms of the nutrition situations and the amount of mental stress tolerated (14).…”
Section: Discussionmentioning
confidence: 88%
“…However, the quality of the included studies was low, and results were inconsistent. Smaller trials evaluating both Hatha yoga (34,35) and vibration therapy (36) have had promising results; however, statistical power was small and more studies would be needed before we can be confident regarding the degree of effectiveness.…”
Section: Peripheral Neuropathymentioning
confidence: 94%